The war for China's wallet profiting from the new world order - Rein, Shaun (Boston Walter de Gruyter Inc, 2018)
Post-financial crisis, China has emerged as the largest or second largest trading partner for most countries. It has become the second largest market for Fortune 500 companies like Starbucks, Apple, and Nike and drives growth for Hollywood and commodity products. Yet the profits come at a price for countries and companies alike-they must adhere to the political goals of Beijing or else face economic punishment or outright banishment. Using primary research from interviews with hundreds of business executives and government officials, The War for China's Wallet will help companies understand how to profit from China's outbound economic plans as well as a shifting consumer base that is increasingly nationalistic. The countries and companies that get it right will benefit from China's wallet but those that do not will lose out on the world's largest growth engine for the next two decades.
xxv, 185 pages ; 23 cm
Keywords: Economic development--China.